The Urgency of Civic Education and Religious Character Education for Early Childhood in Indonesia - Choirul Mahfud; Niken Prasetyawati; Dyah S.Y Agustin; Ni Wayan Suarmini; Enie Hendrajati (Jurusan PGMI FTIK IAIN Metro Lampung, 2019)
Discussing the urgency and relevance of civic education and religious character education from an early age has several challenges as well as opportunities. The research in this paper is qualitative with an analytical descriptive approach using documentation methods. The general objective of this study is to understand not only the urgency but also the relevance of citizenship education and religious character education from an early age in Indonesia? What are the challenges and opportunities for implementing civic education and religious character education for an early age in Indonesia? In general, strengthening civic education and religious character education from an early age in Indonesia is still important because this is part of a process that has never been completed. This is relevant to the spirit of change and sustainability from era to era. In this case, the challenges can be said to be not small. More than that, the opportunity may also be greater to be optimized for the realization of unity in diversity and the progress of the nation.